Interdisciplinarity as an opportunity in Argentinian and Ecuadorian writing groups. Issue 2 (23rd February 2021) - Colombo, L.; Rodas, E. L.
ABSTRACT: At the university level, writing groups have shown to be useful to teach and learn research writing as well as to advance academic-scientific publication and to discover collaboration opportunities among members from different disciplinary fields. At the same time, peer review, an important practice in the academic sphere, is learned within the groups through mutual peer feedback. A key feature of a writing group's formation and progress is connected to how it is organised. One of the variables that seems to influence a group is interdisciplinarity. Nevertheless, the impact of the greater or lesser disciplinary distance in a group's functioning has not been analysed in depth to determine its advantages or disadvantages. This article analyses interdisciplinarity of writing groups in two Latin American countries. In Argentina, the writing groups were formed by master's and doctoral students in the process of writing their thesis, while the writing groups in Ecuador were formed by early career academics and experienced research professors. The analysis of interview and group session transcriptions of the groups in both countries indicates that disciplinary distance mainly presents advantages if the distance is not too great, if there is, as one member put it, a 'close distance.' In this sense, research writing becomes, it seems, a meeting point for members, facilitating enriching exchanges.